Second Language Learner Knowledge of Verb–Argument Constructions: Effects of Language Transfer and Typology. Issue 4 (December 2014) - Römer, Ute; O'Donnell, Matthew Brook; Ellis, Nick C.
Abstract This article examines second language (L2) learner knowledge of English verb–argument constructions (VACs), for example, the 'V against n' construction. It investigates to what extent constructions underpin L2 learners' linguistic competence, how VAC mental representations in native speakers and learners differ, and whether there are observable effects of the learners' first language. Native speakers of English and advanced learners of 3 different first language backgrounds (Czech, German, Spanish) were asked to generate the first verb that came to mind to fill the gap in 20 sparse VAC frames like "she ____ against the…." The comparison of learner and native speaker verb responses highlights crosslinguistic transfer effects as well as effects of language typology that impact verb semantics (cf. Talmy, 1985). Our findings suggest that learners whose L1 is, like English, satellite‐framed (here Czech and German) produce more target‐like verbs than learners whose L1 is verb‐framed (here Spanish).